Implementasi Metode Pembelajaran Peer Tutoring dalam Meningkatkan Prestasi Belajar PAI Siswa di SMP N 2 Tilatang Kamang Kabupaten Agam - Andini, Zulfia; Deswalantri, Deswalantri (Darul Yasin Al Sys, 2025)
This study aims to explore the implementation of the peer tutoring method in improving students' academic achievement in Islamic Education (PAI) subjects, particularly in the topics of prayer and dhikr. Peer tutoring is a learning method in which more capable students help their peers who are experiencing difficulties in understanding the subject matter. This research is motivated by the low academic achievement of students, which is caused by several factors, including teacher-centered learning processes and the lack of student involvement in the teaching and learning process. These factors contribute to the low academic performance of students in SMP N 2 Tilatang Kamang, especially in class VII-2, as well as the significant number of students who have difficulty understanding the teacher's explanations. This research adopts a qualitative approach with a descriptive method to provide an in-depth description of the process and results of implementing the peer tutoring method. The study focuses on problems based on facts found in the field. Data were collected through observation, in-depth interviews, and document analysis in class VII-2 at SMP N 2 Tilatang Kamang, Kabupaten Agam. The research participants consisted of students and PAI teachers involved in the peer tutoring program. The results of the study show that the implementation of the peer tutoring method provides significant benefits in improving students' academic achievement, including enhanced understanding of the material, active engagement in the learning process, and increased self-confidence and motivation to learn. Tutors also gain improved communication and leadership skills. However, this study also identifies several challenges, such as the need for adequate training for peer tutors and continuous support from teachers. The conclusion of this research is that the peer tutoring method has great potential to improve students' academic achievement if implemented with proper support. Recommendations for more effective implementation include developing training programs for peer tutors, increasing teacher involvement, and continuous monitoring and evaluation of the learning process.